THE RELATIONSHIP BETWEEN DECREASED COGNITIVE FUNCTIONS AND THE LEVEL OF PROINFLAMMATORY CYTOKINES IN PATIENTS WITH ALZHEIMER’S DISEASE, VASCULAR DEMENTIA, AND MILD COGNITIVE DISORDER - Olha S. Chyniak; Olga Ye. Dubenko; Olexander О. Potapov (Східноукраїнський медичний журнал, 2021)
Introduction. Alzheimer's disease (AD) is a degenerative disease that leads to dementia symptoms [1, 2]. Histopathological signs of AD are amyloid plaques in the brain, mainly consisting of fibrillary forms of amyloid β-peptide-40 (Aβ-40) and amyloid β-peptide-42 (Aβ-42). Neutrophils are the main targets for IL-17 in the central nervous system (CNS) that promote inflammation and damage to CNS tissues, and may play an important role in the development of AD pathology. Interleukin 23 (IL‑23) synergizes with IL-6, IL-1 and is involved in the differentiation of Th17 cells in a pro-inflammatory context.